Epistemic injustices in clinical communication: the example of narrative elicitation in person‐centred care. Issue 1 (28th October 2020) - Naldemirci, Öncel; Britten, Nicky; Lloyd, Helen; Wolf, Axel
Abstract: The increasing popularity of the term 'person‐centred' in the healthcare literature and a wide range of ideals and practices it implies point to the need for a more inclusive and holistic healthcare provision. A framework developed in a Swedish context suggested narrative elicitation as a key practice in transition to person‐centred care. Initiating clinical communication by inviting people to tell their stories makes persistent yet often subtle problems in clinical communication visible. By drawing upon an observational study on narrative elicitation and vignette‐based focus group interviews with nurses, our aim is to trace 'credibility deficits' (Fricker 2007. Epistemic Injustice. Power and the Ethics of Knowing. Oxford: Oxford University Press) and 'credibility excesses' (Medina 2011, Social Epistemology, 25, 1, 15–35, 2013, The Epistemology of Resistance: Gender and Racial Oppression, Epistemic Injustice, and the Social Imagination. Oxford: Oxford University Press) in narrative elicitation. We argue that narrative elicitation may be one way to tackle epistemic injustices by giving voice to previously silenced groups, yet it is not enough to erase the effects of 'credibility deficits' in clinical communication. Rather than judging individual professionals' success or failure in eliciting narratives, we underline some extrinsic problems of narrative elicitation, namely structural and positional inequalities reflecting on narrative elicitation and the credibility of patients. 'Credibility excesses' can be useful and indicative to better understand where they are missing.